Correctional Programs in Reform and Rehabilitation Centers in the Southern Governorates of Palestine and Their Impact on the Level of Psychological and Social Adjustment from the Perspective of Recidivist Inmates - Aldaya, Reda Fayez; Islaieh, Abdelrahman Ibrahim; Samah , Rosni Bin; Ali , Myra Aidrin Mohd; Amin , Ahmad Fuad Mohamad (Dirasat: Human and Social Sciences, 2024)
Objectives: This study investigated the impact of rehabilitation programs on the psychological and social adaptation of recidivists in Palestine which was achieved by examining the level of implementation of rehabilitation programs and the psychological and social adaptation in different correction and rehabilitation centres. Methods: A systematic research design was adopted to achieve the goal of objective normative inquiry. Data was collected through a questionnaire and analyzed using descriptive analysis and linear regression. This encompassed measuring correctional program effectiveness and psychological-social compatibility among 237 recidivist inmates in the southern governorates, chosen through simple random sampling. Results: The results of the study showed a high level of application of the correctional programs used from the point of view of the inmates of recidivism for crime, according to the relative weight of 73.6%. and social, by 12.3%, as well as a significant effect of the variable of age and the variable of educational level as extraneous variables on the relationship between the correctional programs scale and the psychological and social adjustment scale Psychological and social. Conclusions: The study concluded the presence of a high level of implementation of rehabilitation programs as perceived by recidivists, while also indicating a low level of psychological and social compatibility among recidivists. The study further concluded a significant impact of rehabilitation programs on psychological and social compatibility, as well as the influence of age and educational level. However, the study found no significant impact of social status and the duration of punishment.